Investigating the usage of vocabulary learning strategies among high and low proficiency Malay undergraduates / Lee Ai Chat, Ng Lee Luan and Ngeh Hoong Eng - Chat, Lee Ai; Luan, Ng Lee; Eng, Ngeh Hoong (Universiti Teknologi MARA Shah Alam, 2017)
This study aims to determine and compare the types of Vocabulary Learning Strategies (VLS) use by Malay students with high (HPML) and low proficiency (LPML) in Mandarin as a foreign language (MFL) in the Malaysia tertiary education context. This research was conducted base on a quantitative approach and it involved 330 respondents. Results from the analysis of collated quantitative data showed that the HPML used VLS at high frequency level, whereas the LPML used them at medium frequency level. Besides, the findings also revealed that the HPML students tend to use "recall the meaning of Mandarin words" strategy; whereas those from the LPML frequently used strategy such as "saying new Mandarin words repetitively". The findings show that students from both the HPML and LPML groups rarely use "flash cards to learn new Mandarin words". The findings of the study were also used to outline pedagogical, theoretical and methodological implications.